PENGARUH KEPUASAN WAJIB PAJAK TERHADAP KEPATUHAN WAJIB PAJAK - Suharto Suharto (Derivatif : Jurnal Manajemen, 2011)
Abstract Tax reforms that have been annouced by the goverment since early 2000, including the application of modern tax administration sistem. Application of a new sistem of tax composed of so many parts, some of which are merging service functions income tax, VAT and rthe united nations integrated services in places, the appointment of account representative to provide personalized service to taxpayers and a more transparent process in the agency offices the tax.  The study population was registered taxpayers in KPP City Metro. Relative to the large number of tax payers, researchers used a purposive sample by the number of 50 respondents. The variables in this study include satisfaction as independent variables and compliance as the dependent variable. Methods of data collection methods used were questionnaires and interviews to support the questionnaire that has been deployed. Data analysis methods used is descriptive analysis and Spearman Rank analysis techniques with the help of SPSS 17.0 statistical program.  Results showed that satisfaction with the taxpayer on the application of modern tax administration sistem is quite high. Results of analysis using the Spearman Rank shows that ρ count of greater that 0.546 ρ tables (0363) to fit the testing criteria that is if ρ count > table ρ (α = 1%) then the null hypothesis (Ho) is rejected and alternative hypothesis (Ha) are accepted. Alternative hypothesis proposed in the study is the satisfaction of the taxpayer significant affect on taxpayer compliance application of modern tax administration sistem.  Based on these findings, the authors propose suggestions to the leadership of Metro City KPP DAPT improve quality of service to taxpayers, especially at the help desk, the inspection process as well as information about how the tax compulation. It aims to increase taxpayer satisfaction and leads to an increase taxpayer compliance.  Keywords: Satisfaction, Compliance, Tax Payer.